First-principles study of electronic transport coefficients of point-defective metallic species: aluminum and its bimetallic alloys. (19th March 2019) - Choi, Garam; Kim, Hyo Seok; Park, Sang Hyun; Cha, JinHyeok; Chung, In; Lee, Won Bo
Abstract: The electronic transport coefficients, such as electrical and thermal conductivity and the Seebeck coefficient, of aluminum (Al) and its bimetallic alloys (Al2 Cu, Al12 Mg17, AlZr3 ) with point defects are studied based on first-principles calculations and the Boltzmann transport equation. Defects in alloys can lead to changes in electronic structures, such as group velocity and density of states, resulting in deviations in transportation distributions. In this manner, these defects affect electronic transport coefficients. In this study, changes of transport coefficients by defects are described by temperature and chemical potential energy. The defects have a negative impact on the conductivity of metal alloys. However, it is found that this effect is relatively small at certain Wyckoff sites. In addition, it is noted that the defects may lead to useful features in terms of thermoelectricity. This study will support understanding and designing the metal alloys by theoretical anticipations of the transport coefficients by defects, according to changes of temperature and chemical potential energy.